A new species of Eschweilera (Lecythidaceae) from the Brazilian Atlantic Forest - Ribeiro, Michel; Mori, Scott A.; Alves-Araújo, Anderson; Peixoto, Ariane L. (Phytotaxa, 2016)
Eschweilera sphaerocarpa (Lecythidaceae) is described here as a new species for science. It is closely related to Eschweilera complanata. Due to an area of occupancy of less than 10 km² this species is regarded as endangered according to the standards of the IUCN. This paper provides a description, illustration and, comments on geographic distribution and ecology. Additionally, a diagnostic key to the species of Eschweilera section Tetrapetala is provided.